Enhancing Performance and Productivity Through Innovation in Business Management - Vittorio, Roy; Rajuddin, Wa Ode Nursaadha; Dewi, Ni Luh Yulyana (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
Innovation in business management plays a key role in improving organizational performance and productivity. This research highlights various strategies and approaches that companies can implement to drive innovation and achieve competitive advantage. The primary focus of this research is on how companies can integrate advanced technology and innovative management practices to optimize business processes, improve operational efficiency, and spur growth. The methodology used includes an analysis of case studies of companies that have successfully implemented innovation in their management, as well as a review of current literature related to this topic. The research results show that companies that proactively adopt new technology and develop a culture of innovation tend to have better performance and higher productivity compared to those that do not. In addition, this research also found that employee involvement and visionary leadership are important factors in driving innovation. Thus, this research provides valuable insights for business practitioners and academics in understanding the importance of innovation in business management and how to implement it effectively to achieve desired results. At the end of the research, it is recommended that companies continue to invest in research and development, as well as adopt a flexible management approach to remain competitive in an ever-changing business environment.